Dental Aesthetic Index among Nepalese Orthodontic Patients (Orthodontic Journal of Nepal, 2015)
Introduction: Orthodontic indices are used for the assessment of malocclusion, its severity level, and treatment need. Dental Aesthetic Index (DAI) is a simple, valid and reliable index commonly used for epidemiological survey and initial screening of the orthodontic patients.Objective: To evaluate the frequency and severity of malocclusion and orthodontic treatment need among Nepalese patients using DAI and to compare the treatment need between gender groups.Materials & Method: 150 pairs of maxillary and mandibular pre-treatment orthodontic study models of 59 male and 91 female patients with permanent dentition were randomly selected from the Department of Orthodontics, Kantipur Dental College. Ten occlusal traits of DAI were assessed on each pair of study models using graduated periodontal probe and metallic scale by a single examiner. Cumulative DAI scores were calculated according to standard DAI method to differentiate the severity of malocclusion and orthodontic treatment need.Result: About 60% of the sample presented severe or very severe (handicapping) malocclusions indicating highly desirable or mandatory treatment need. 21.3% had definite malocclusion that required elective treatment need, 19.3% had normal occlusion with no or slight treatment need. There was no statistically different mean DAI scores between male and female samples (p=0.116)Conclusion: Most of the samples were in great need of orthodontic treatment with very severe malocclusions. Male samples had greater percentage of ‘very severe’ malocclusion than female. Malocclusion was characterized with high frequency of anterior incisal irregularity, maxillary overjet, midline diastema. DAI can be used as a screening tool rather than the decision making tool.